(untitled) (Tempo e Argumento, 2009)
This article presents an overview of the fights for amnesty which took place in Rio Grande do Sul during the second half of the 70’s. It places such fights amidst a vigorous social process which was contemporary to the government opening project (Abertura) and relates them to the taking over of mass work and to new political leading figures who were coming up. It also highlights the pioneering participation of women and the importance of historical research which was attentive to representations and to memory struggles around dictatorship and redemocratisation p rocesses.